Mempersiapkan Generasi Z Menghadapi Tantangan Karir: Program Pengabdian Masyarakat Di Gereja Kristen Indonesia Kebonjati Bandung - Lu, Cen; Munthe, Rusli Ginitng; Nur, Nur; Mariana, Ana; Lunandi, Yenny Yuniawaty; Tjun, Lauw Tjun (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Generation Z faces significant challenges in planning their careers in the digital era, characterized by the paradox of choice, social pressures, and labor market uncertainty. This Community Service Program, organized by the Undergraduate Management Program of Maranatha Christian University in collaboration with GKI Kebonjati, aimed to assist Generation Z in understanding the importance of early career management. The program included seminars, interactive discussions, and the application of the Johari Window approach to enhance self-awareness, passion discovery, and career decision- making skills. The evaluation results showed a significant improvement in participants’ understanding, confidence, and readiness to face the job market, with the average post-test score (4.04) notably higher than the pre-test (3.30). This program highlights that career education and mentoring effectively support Generation Z in navigating dynamic labor market changes and planning a meaningful future aligned with their potential.